2022
DOI: 10.1111/jocs.16948
|View full text |Cite
|
Sign up to set email alerts
|

Transit‐time flow measurement parameters after protamine infusion in CABG surgeries

Abstract: Objective The objective of this study is to evaluate protamine sulfate effects on graft's blood flow by comparing transit‐time flow measurement (TTFM) values before and after protamine administration. Methods This is an observational study with data collected between years 2018 and 2020. Immediate graft patency was evaluated using TTFM. Only patients with TTFM parameters registered before and after protamine infusion were included. The main three parameters studied were:  mean graft flow  (MGF),  pulsatility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In a retrospective analysis of the REQUEST database [ 7 ], Leviner et al [ 24 ] showed that MGF and PI were unchanged in arterial grafts between the two measurements while there was a slight increase in MGF and slight decrease in PI in venous grafts after protamine administration. Dallan et al [ 25 ], reporting the results of TTFM measurements in 575 patients with 1686 grafts (59.6% SVG) showed no statistically significant difference in either MGF or PI in arterial grafts after protamine infusion. They also saw no difference in post protamine MGF in venous grafts but a slight increase in PI.…”
Section: Changes In Ttfm Parameters After Protaminementioning
confidence: 99%
“…In a retrospective analysis of the REQUEST database [ 7 ], Leviner et al [ 24 ] showed that MGF and PI were unchanged in arterial grafts between the two measurements while there was a slight increase in MGF and slight decrease in PI in venous grafts after protamine administration. Dallan et al [ 25 ], reporting the results of TTFM measurements in 575 patients with 1686 grafts (59.6% SVG) showed no statistically significant difference in either MGF or PI in arterial grafts after protamine infusion. They also saw no difference in post protamine MGF in venous grafts but a slight increase in PI.…”
Section: Changes In Ttfm Parameters After Protaminementioning
confidence: 99%